Pengembangan dan Validasi Metode Pengukuran Preferensi dan Pola Aktivitas Ruang Terbuka Sebelum dan Setelah Pandemi di Kampus ITB Ganesha - Firmansyah; Kusuma, Bintang Nidia; Allo, Ira Prayuni Rante; Triningsih, Endang; Widiyani (Jurnal Lanskap Indonesia, 2025)
Campus open spaces play an important role in supporting social interaction and creating an integrated campus environment. Their provision is adjusted to the function and needs of students for outdoor spaces. This study aims to develop a method used to measure student preferences and activity patterns in utilizing campus open spaces. This study focuses on the development and validation of methods for measuring student preferences and activity patterns in campus open spaces through the design of a questionnaire as a measurement instrument, in order to obtain results that can represent the overall pattern of campus open space utilization. The data used in the design and preparation of this questionnaire are the factors and indicators that form campus open spaces, which have been identified in previous studies. Data were collected through the distribution of questionnaires, to be analyzed using statistical tests in the next stage. Statistical tests were conducted to test the correlation between the function of open spaces, factors, and indicators of campus open spaces with the landscape elements that form them. Through this statistical test, elements that have a significant correlation in creating campus open spaces that are in accordance with student preferences can be identified. The results of this study include the methods used for data collection that can later be used in statistical tests, in order to gain further insight into the preferences and patterns of campus open space utilization by students.